Price Distortions and Competitiveness of Cotton Production in Pakistan - Waqar Akhtar,; Muhammad Qasim,; Abid Hussain,; Nadeem Akmal,; Hassnain Shah,; Muhammad Ather Mahmood,; Rashid Saeed, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The research is conducted to determine the cotton price distortions, as well as competitiveness at national and international levels. National competitiveness has been measured by using the nominal protection coefficient (NPC) and benefit-cost ratios for the period 2008-09 to 2018-19. To gauge international competitiveness, trade base indices under the revealed comparative advantage approach are used. A comparison of the international competitiveness of Pakistan with major cotton-exporting countries has also been made. The results of this research revealed that at the national level cotton producers in Pakistan faced implicit taxation for most of the years during the study period, as NPCi averaged at 0.87 as an import substitution crop. Export parity prices were slightly less or equal to the domestic prices by varying degrees as NPCe averaged at 1.06. The production cost grew at the rate of 12.3% per annum, while cotton output prices grew at the rate of 8.4 percent per annum. Consequently, a decrease was registered in the benefit-cost ratio during the study period. Pakistan has experienced comparative and competitive advantage for cotton as indicated by results of revealed comparative advantage (RCA) indices. A comparison of Pakistan’s indices with main exporters/competitors demonstrated that Pakistan has a relatively higher comparative and competitive advantage for cotton. However, Pakistan’s international competitiveness exhibited a declining pattern since 2011-12. This result is consistent with the national level scenarios as the benefit-cost ratio has declined over this period. It can be concluded that productivity growth and a reduction in input costs are needed to improve overall competitiveness in cotton production and trade.